Respuestas

  • Usuario de Brainly
2013-05-12T19:31:41+02:00
X + 3= -9
Pasas las incognitas a un lado:
X=-9-3
X=-12


X+(-7)=5
X-7=5
X=5+7
X=12


-6+x=2
X=2+6
X=8


X-5=6
X=6+5
X=11


Saludos
  • Usuario de Brainly
2013-05-12T20:05:25+02:00

Resolvamos tenienDo en cuenta la ley de SigNos :

 

  (+) * (-) = -

  (-) * (-) = +

   

    a)    x + 3 = -9

               x = -9 - 3

                 x = -12           ... Rpta 

 

   b)      x + (-7) = 5

              x - 7 = 5

                x = 5 + 7

                x = 12      ... Rpta

 

  c)       -6 + x = 2

                  x = 2 + 6

                   x = 8       ... Rpta

 

 d)        x - 5 = 6

                x = 6 + 5

                  x = 11          ... Rpta

 

Ojalá te sirva , SaLuDos  =)''